Treatment of acute myocardial infarction in the sub-arctic region of Norway. Do we offer an equal quality of care? - Norum, Jan; Hovland, Anders; Balteskard, Lise; Trovik, Thor; Haug, Bjørn; Hansen, Finn Henry; Alterskjær, Sissel; Madsen, Pål; Olsen, Frank (International Journal of Circumpolar Health, 2017)
Source at https://doi.org/10.1080/22423982.2017.1391651 Patients, relatives, healthcare workers and administrators are concerned about the quality of care offered. We aimed to explore the treatment of acute myocatrdial infarction (AMI) in Northern Norway, compare it with the national figures, and document whether there is an equal quality of care or not. The retrospective study included data on patients' treatment for AMI. The following sources were employed. The Norwegian Patient Registry, National Quality of Care Database, Norwegian Myocardial Infarction Registry and data from the National Air Ambulance Services of Norway. The period 2012-2014/15 was studied and the variables were: incidence of AMI, gender and age adjusted rates of AMI and revascularization (PCI, CABG) based on patient's place of living (according to hospital catchment area) and 30-day survival rate. The annual incidence of AMI was 9% higher in the northern region. Significant incidence variations (2.7 – 5.9 AMI/1000 inhabitants) between the hospitals' catchment areas were revealed. The 30-day survival rate varied between 85.1 – 92.1% between hospitals. The variation in revascularization/AMI rate was 0.72 – 1.54. Air amublance services' availability varied through the day. In conclusion, significant variations in the AMI rate and an unequal service within the region was revealed.